The Association between Conditional Cash Transfer Programmes and cohort fertility: Evidence from Brazil - Camila Ferreira Soares; Everton Emanuel Campos de Lima (Comparative Population Studies (CPoS), 2021)
Brazil's Bolsa Família Programme (BFP) aims to combat poverty and social inequalities through monetary transfers to families. A much-discussed indirect effect of the programme was its correlation to the fertility of the beneficiary families. In this paper, we use a cohort fertility approach with parity progression ratios that differs from existing literature, which mainly used period fertility measures, to better understand the relationship between fertility and the BFP. This study analyses the relationship between the BFP and the reproduction of Brazilian women. We use data from the 2010 Brazilian micro-censuses, the only census after the start of the BFP in 2004, to reconstruct the childbirth history of women with incomplete reproductive cycles (women aged 25 to 29), and estimate parity progression ratios (PPRs) and cohort fertility rates (CFR). In addition, we estimate propensity score matching (PSM) models comparing fertility outcomes of beneficiaries and non-beneficiaries of the programme. Our results show distinct differences in CFRs and PPRs. On average, BFP beneficiaries had more children than women not covered by the programme. This finding remained consistent even after controlling for educational gradients and other covariates. Our empirical findings show that women opt for a 'rational' strategy, where they tend to have children in more rapid succession up until three children. These findings contradict the recent literature that has not found any correlation between BFP and fertility. The results also suggest that cohort analyses may fill certain gaps left by previous studies of period fertility. This paper is one of a few that have analysed the relationship between a conditional income transfer programme and cohort measures in Brazil.
urn:nbn:de:bib-cpos-2021-08en9
Keywords: 300; Bolsa Família Programme; Cohort fertility; Parity progression ratio; Propensity Score Matching